Democracy, state capacity and the governance of COVID-19 in Asia-Oceania - Croissant, Aurel, 1969-; Hellmann, Olli, 1979- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines the public health responses to the COVID-19 pandemic in the Asia-Oceania region and their implications for democratic backsliding. The contributions discuss three key questions: How did political institutions in Asia-Oceania create incentives for effective public health responses to the COVID-19 outbreak? How did state capacities enhance governments' ability to implement public health responses? How have governance responses affected the democratic quality of political institutions and processes? Together, the analyses reveal the extent to which institutions prompted an effective public health response and highlights that a high-capacity state was not a necessary condition for containing the spread of COVID-19 during the early phase of the pandemic. By combining quantitative and qualitative analyses the volume also shows that the effect of the COVID pandemic on the quality of democratic institutions has been uneven across Asia-Oceania. Guided by a comprehensive theoretical framework this will be an invaluable resource for scholars and students of political science, policy studies, public health and Asian studies"--
Introduction : democracy and state capacity during times of crisis / Aurel Croissant & Olli Hellmann -- Policy responses to the COVID-19 pandemic : an aggregate level comparative analysis / Jale Tosun -- COVID-19 and democracy : creeping autocratization? / Aurel Croissant & Lars Pelke -- Closing the borders to COVID19 : democracy, politics and resilience in Australia and New Zealand / Jennifer Curtin & Dominic O'Sullivan -- Containing COVID-19 in South Korea and Taiwan : state capacity and geopolitics / Yin-wah Chu -- Navigating the early impacts of COVID-19 : South Pacific viewpoints from Fiji and Samoa / Audrey Aumua, Saunimaa Ma Fulu-Aiolupotea, Tamasailau Suaalii-Sauni & Tim Fadgen -- The pandemic and competitive authoritarianism in India / Rahul Mukherji and Seyed Hossein Zarhani -- Economy first : Indonesia's calculated underutilization of state capacities and democratic resources in the early phase of COVID-19 / Marcus Mietzner -- COVID-19 in the Philippines and Cambodia : rising autocracy and weak state capacity / Erik Martinez Kuhonta, Keovathanak Khim & Tynarath Huon -- Singapore and Hong Kong : the effect of trust in high-capacity hybrid regimes / Mathew Y.H. Wong & Adrian M.H. Lam -- Proactive responsiveness and institutionalization in Vietnam's offensive against COVID-19 / Nhu Truong -- China's response to the COVID-19 Pandemic. Navigating internal and external challenges / Heike Holbig.
Keywords: COVID-19 (Disease) -- Government policy -- Asia; COVID-19 (Disease) -- Government policy -- Oceania; COVID-19 Pandemic, 2020- -- Asia; COVID-19 Pandemic, 2020- -- Oceania; POLITICAL SCIENCE / General; POLITICAL SCIENCE / Government / Comparative